Phenethyl isothiocynate attenuates Parkinson's disease and improves performance in hanging wire, rotarod and actophotometer test & dopamine levels in rats via inhibiting HDAC-1 - Nikhil More; Angel Godad (Brain Disorders)
Parkinson's disease (PD) is a neurodegenerative disorder that affects overall motor activity due to the loss of dopaminergic neurons in the SNpc (Substantia Nigra Pars Compacta) region of the brain. Despite incessant research and development of new therapeutic agents, management of PD is still a troublesome affair. Histone Deacetylase 1 (HDAC-1-1) is an epigenetic regulator which plays an important role in the pathogenesis of PD. In the present study, we hypothesized that Phenethyl isothiocyanate (PEITC), a potent inhibitor of HDAC-1-1, may ameliorate PD. Efficacy of PEITC was evaluated in rotenone-induced PD model in Male Wistar Male rats. Rotenone (2.5mg/kg) was injected intraperitoneally for 28 days to all the groups except Normal Control. The administration of test drug PEITC (5, 10 & 20 mg/kg) and standard drug levodopa with carbidopa was given for 28 days. The animals were subjected to various behavioural parameters to assess motor co-ordination and groups treated with PEITC showed better performance with P<0.05 when compared with rotenone treated group. Further, HDAC-1 levels in brain tissue homogenate and histological analysis were performed. Prophylactic treatment of PEITC attenuated motor dysfunction in dose dose-dependent manner. Furthermore, there was a significant decrease in HDAC-1 levels in brain tissue homogenate in the treatment group. Histological analysis revealed a decrease in neuronal loss and vacuolization. Results of this study suggest potent anti-Parkinsonism activity of PEITC in Rotenone induced rat model of PD.